1998
DOI: 10.1126/science.281.5379.978
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Oceanic Volcanic Glass: Textural Evidence of Microbial Activity

Abstract: The subsurface biosphere may constitute as much as 50 percent of Earth's biomass. Direct and indirect evidence suggests that an extensive biosphere exists in the rocks below the sea floor. This survey of basalts of the Atlantic, Pacific, and Indian Oceans supports the hypothesis that bacteria have colonized much of the upper oceanic crust, which has a volume estimated at 10(18) cubic meters. Although this is the largest habitat on Earth, its low abundance of bacteria constitutes much less than 1 percent of Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
226
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(241 citation statements)
references
References 13 publications
11
226
0
4
Order By: Relevance
“…Endolithic microborings are well known from silicified carbonate sediments younger than ca 1650 Myr (e.g. Zhang & Golubic 1987) and have been reported from the glassy margins of pillow basalts in modern settings (Fisk et al 1998; Banerjee al. 2004).…”
Section: Endoliths and The Warrawoona 'Microtubes'mentioning
confidence: 99%
“…Endolithic microborings are well known from silicified carbonate sediments younger than ca 1650 Myr (e.g. Zhang & Golubic 1987) and have been reported from the glassy margins of pillow basalts in modern settings (Fisk et al 1998; Banerjee al. 2004).…”
Section: Endoliths and The Warrawoona 'Microtubes'mentioning
confidence: 99%
“…Early molecular diversity studies of hydrocarbon-and chlorinatedsolvent contaminated aquifers revealed the presence of microorganisms belonging to known bacterial phyla as well as divergent lineages affiliated with candidate divisions or defining novel candidate-division-level groups (Dojka et al 1998). By contrast to hydrocarbonpolluted aquifers, organic matter is scarce in aquifers associated with deep underground systems, such as deep mines (Pedersen 2000) or the deep sub-seafloor (Fisk et al 1998, Edwards et al 2005. Microbial life in such systems is thought to be largely based on chemolithoautotrophy and metabolic rates may be extremely low (Parkes et al 2005, Schippers et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…These observations raise intriguing questions about the role that microorganisms play in biogeochemical cycling in basalts. Biological alteration of basalt by microorganisms has been the focus of numerous studies, with compelling evidence suggesting that they do play a part in this process (Thorseth et al, 1995;Giovannoni et al, 1996;Fisk et al, 1998Fisk et al, , 2003Torsvik et al, 1998;Furnes and Staudigel, 1999;Furnes et al, 2001Furnes et al, , 2004Banerjee and Muehlenbachs, 2003).…”
Section: Introductionmentioning
confidence: 99%